Exchange Obligation: its concept and scope : (Analytical study) - Shalaw Azad Ali; Esmail Namiq Husen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
In writing this research, the researcher implemented inductive and analytical approaches to the subject of the exchange obligation (L'obligation Cambiaire), with the aim of defining its concept and scope, and to explain its different types and connections with the non-exchange obligations. The researcher concludes that the particular rules of exchange obligations differ from the ordinary obligation rules in terms of source, object, creditor protection, the origins of the obligation, as well as in terms of trading, solidarity, and the end of the obligation. Later on, the researcher proposes a number of recommendations. The most important recommendation is that both Kurdistan Region and Iraqi legislators should review the rules for exchange obligations and reformulate them in such away they clearly address the definition, characteristics and provisions of the exchange obligation completely independent from the general rules. The reason is that this obligation has a special nature, in which mix-ups in its provisions may affect its nature, and weaken its importance and legal stand.